KETIDAKEFEKTIFAN KALIMAT BAHASA INDONESIA DALAM DISKUSI PADA MATA KULIAH SEMINAR PENDIDIKAN BAHASA DAN SASTRA INDONESIA MAHASISWA ANGKATAN 2010 C - Kulup, Luluk Isani (Buana Bastra, 2014)
Abstract A form of discussion, such as group, seminar, and debate, needs an interactive situation. The exchange of mind in the discussion is planned so that all participants of discussion could have one perception. The situation of discussion could take place well if all participants such as moderator, speaker, and audience have a good cooperation. The cooperation could be arranged well if all participants use bahasa agreements before implementing the discussion. However, some participants could break the agreement becuase they do not use a proper sentence. The effect of breaking the agreement is a never ending discussion. The students also have this case when they have a discussion of seminar course. This course needs a special skill. The skill is to connect, analyze, and present each of the concepts in front of colleagues. Besides, the presenter should present a paper with an understandable sentences, efficient sentences, and communicative sentences. Key Words: Effective sentence, discussion, seminar course.